(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Several clinical and laboratory observations are consistent with the hypothesis that hypokalemia might be a risk factor for the development of ischemic stroke in humans. Objectives:To evaluate the level of serum potassium in ischemic stroke patients and its relation to non-stroke patients and those with hypertension. Methods: Serum potassium was estimated from one hundred newly discovered first-life ischemic event of acute ischemic stroke patients and one hundred control patients with an attempt to evaluate the its level in ischemic stroke and the relation to hypertension. Normal value of serum potassium in both sexes was considered as 3.5-.5.5 mmol/L. Results:Mean serum potassium level of stroke patients was significantly lower than that of control group (3.89±0.67 versus 4.19±0.56, p=0.0001). Hypokalemia was found in 23 (23%) patients with stroke compared to 7 (7%) of the control group. The Mean serum potassium in hypertensive patients was significantly lower than those without hypertension (3.91 ±0.65 versus 4.2 ±0.54). The mean serum potassium for hypertensive stroke patients was significantly lower than non-hypertensive stroke patients (3.79±0.78 versus 4.26±0.72), while there was no significant difference among the control hypertensive and non-hypertensive subjects (4.05±0.57 versus 4.43±.40). Conclusions:Serum potassium should be taken in consideration as low levels are significantly associated with ischemic stroke with hypertension. Keywords:Serum Potassium, ischemic stroke